2020
DOI: 10.4103/1319-4534.310415
|View full text |Cite
|
Sign up to set email alerts
|

Do Saudi parents have sufficient awareness of pediatric eye diseases in Riyadh?

Abstract: PURPOSE: The current study aimed to assess Saudi parents' awareness regarding pediatric eye diseases that can be screened and treated. METHODS: A cross-sectional study was conducted in Riyadh, Saudi Arabia. Targeted participants were selected randomly. An online questionnaire was used for data collection. A Chi-ANOVA test was used with considering a confidence interval of 95%. RESULTS: Of 1500 participants, 1070 (71%) Saudi adults responded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
4
17
0
Order By: Relevance
“…In this self-reported cross-sectional study, we aimed to assess parents' awareness and attitude toward pediatric eye diseases. A previous study reported poor knowledge in 78.2% of parents [ 7 ], whereas another study reported poor knowledge among 91.9% of parents [ 8 ]. Consistently, our findings showed that 72.8% of parents had a low level of awareness regarding pediatric eye diseases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this self-reported cross-sectional study, we aimed to assess parents' awareness and attitude toward pediatric eye diseases. A previous study reported poor knowledge in 78.2% of parents [ 7 ], whereas another study reported poor knowledge among 91.9% of parents [ 8 ]. Consistently, our findings showed that 72.8% of parents had a low level of awareness regarding pediatric eye diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the previous studies regarding this subject reveal the need for further assessment of the knowledge about children's eye diseases among parents and its associated factors to enhance the improvement of their understanding level [ 7 , 8 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations